Mauritania : Urban Infrastructure and Pilot Decentralization Project - Mohan, P.C. (World Bank, Washington, DC, 2012)
The project, implemented between 1996 and 2001 with World Bank funding of US$24 million had two components: (i) a program of poverty-oriented, labor-intensive works subprojects in participating cities, consisting of the rehabilitation or construction of urban infrastructure and community facilities; and (ii) capacity building ( pilot decentralization) at the municipal and national levels. The project capitalized on the work and experience gained by the country, the Region and the Bank through the earlier "highly satisfactory" Construction Capacity and Employment Project (CCEP). The project created approximately 46,281 man-months of temporary jobs- more than twice the projected number. There was a delegation of 125 contract management conventions covering 149 infrastructure construction and/or rehabilitation subprojects completed in 13 cities, which accounts for 85 percent of the urban population or 1.2 million inhabitants. Nouakchott and Nouadhibou consumed 40 percent of the investments, commensurate with their share of the urban population (37 percent). Of the 149 subprojects, 144 were fully executed (5 were under implementation in 2002) targeting the most under-serviced neighborhoods. Two-thirds of the subprojects were for educational and social infrastructure and contributed to the reduction of crowding, improvement of hygiene and security in schools, access to primary health, and, to a lesser extent, access to productive assets. Revenue-generating projects accounted for about 18 percent of the total coat of $15.4 million-these included the rehabilitation and/or construction of new markets, slaughterhouses, livestock enclosures, and taxi stations.